Nonconvulsive Status and Ring Chromosome 20 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Six cases of epilepsy and ring chromosome 20 are reported and 20 additional cases in the literature are reviewed from the National Epilepsy Center, Shizuoka Higashi Hospital, Japan.